2019
DOI: 10.1088/1757-899x/615/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Application of semiotics for health and safety signs comprehension on construction sites in Yola metropolis, Nigeria

Abstract: This study investigates how semiotics can be applied to enhance construction operatives’ health and safety (H&S) signs comprehension in Yola metropolis, Nigeria, with a view to improving on H&S management that will curtail the occurrence of accidents. Adopted ISO (9186-1) questionnaire for testing H&S signs comprehension were administered to 60 construction professionals and operatives that are executing 5 government building projects. Responses were subjected to descriptive and inferential statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Incidents : means all hazard-related events that have been referred to as accidents, mishaps, near misses, occupational illnesses, environmental spills, losses, fires, explosions. 19 – 21 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Incidents : means all hazard-related events that have been referred to as accidents, mishaps, near misses, occupational illnesses, environmental spills, losses, fires, explosions. 19 – 21 …”
Section: Methodsmentioning
confidence: 99%
“…Emergency escape or first-aid sign : a sign that informs people about emergency exits, first-aid, or rescue facilities. 19 – 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that neither the red color nor the graphic content contributed to higher reported accuracy levels, but they were quicker to be identified and comprehended during visual search and scanning activities. Alara et al (2019) investigated how semiotics can be used to enhance the comprehension of construction operatives' health and safety (H&S) signs in the Yola metropolis, Nigeria. They found training, experience and education ranked highly relevant for curbing accidents on construction sites.…”
Section: Comprehension Of Safety Signmentioning
confidence: 99%